Implementation of a DSP Based Impedance Measurement Instrument Using Ellipse Fitting Algorithms - Ramos, Pedro M. (2009)
In this paper, the DSP implementation of an impedance measurement instrument based on ellipse fitting algorithms is described. The system prototype is based on a commercial DSP kit with few external electronics for baseline assessment and requirements definition. The implemented system is tested for impedance magnitudes from 100 Ω up to 15 kΩ, phases in the ±90º range at 1 kHz measuring frequency with extremely good results.